Юридичні аспекти інтелектуальної власності в період глобалізації економічних відносин - Макода, В.С. (Інститут держави і права ім. В.М.Корецького НАН України, 2009)
Освещаются проблемы интеллектуальной собственности, которые все теснее переплетаются с научно-техническим прогрессом, особенно в связи с концепцией инновационного развития. Автор показывает, что интеллектуальную собственность необходимо рассматривать не только как систему правовых норм, но как самостоятельный и активный экономический институт, который влияет на инновационный процесс. Problems of intellectual property all closer interlace with scientific and technical progress, especially in connection with innovative development. Intellectual property must be examined not only as a system of legal norms, but, as an independent and active economic institute which influences on an innovative process. In the conditions of globalization of world economy an important value for successful distribution of new technologies acquires the commercial use of objects of intellectual property, that grew into the effective mechanism of assistance to development of trade, international scientific and technical cooperation.